Purification and characterization of amino acid oxidase l-snake venom Bothrops Brazili “Jergón Shushupe" - Solís, Christian (1999)
An L-aminoacid oxidase was purified from Bothrops brazili snake venom using Sephadex G-100 and CM-Sepahdex C?50 chromatographic method; in both cases 0,1M ammonium acetate pH 6 was used as a eluted. The enzyme was purified 29,3 fold with 30,9% of yield. A homogeneus protein band was achieved by PAGE-SDS, inmunodifusion as well as immunoelectrophoresis. The enzyme was an acid glicoprotein with a molecular weight of 125,7 kd consisting of two subunits of 59,91 kd each, linked by noncovalent bonds. The optimum pH was in the range of 7,5 to 9,0 depending on the L-aminoacid used as substrate. It was a thermoestable protein untill 55 oC, but its activity decreased by alcaline treatment. On the other hand, antibacterial assays using the Grove's method demonstrated that the whole venom as well as its purified enzyme produced a severe action on standardized grown cultures of Staphylococcus aureus, Vibrio cholerae and Streptococcus faecalis.